Time-Based Decision Making for Reperfusion in Acute Ischemic Stroke - Grøan, Mathias; Ospel, Johanna; Ajmi, Soffien; Sandset, Else Charlotte; Kurz, Martin W.; Skjelland, Mona; Advani, Rajiv (Frontiers in Neurology, 2021)
Decision-making in acute ischemic stroke is a complex and time-consuming process. The process of making the clinical decision to treat has been compounded by extended treatment windows. In the setting of acute reperfusion, time is of the essence and chances of a good outcome diminish by each passing minute. The widespread availability of advanced imaging means that treatment can be delayed to no avail rather than being efficaciously expedited. Time delays and individually based non-programmed decision making can prove challenging for clinicians. Visual aids can assist such decision-making aimed at simplifying the use of advanced imaging. Flow charts are one such visual tool that can expedite treatment in this setting. A systematic review of existing literature around imaging modalities based on site of occlusion and time from onset can be used to aid decision making; a more program-based thought process. The use of an acute reperfusion flow chart helping navigate the myriad of imaging modalities can aid the effective treatment of patients.